2010
DOI: 10.1111/j.1539-6924.2010.01463.x
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Environmental Health Risks in the UAE

Abstract: This article presents the results of a comparative environmental risk-ranking exercise that was conducted in the United Arab Emirates (UAE) to inform a strategic planning process led by the Environment Agency-Abu Dhabi (EAD). It represents the first national-level application of a deliberative method for comparative risk ranking first published in this journal. The deliberative method involves a five-stage process that includes quantitative risk assessment by experts and deliberations by groups of stakeholders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 9 publications
1
43
0
Order By: Relevance
“…Finally, following a suggestion made by one of the reviewers, we have performed another robustness check, by using a testing procedure reported in Willis et al (2010) and predicted individual rationality at time 2 using just individual rationality at time 1 and group rationality as predictors (we controlled for age and gender as well). Although this statistical analysis does not address directly our two hypotheses, it allows us to compare the model fit for the simple model (procedure reported in Willis et al, 2010) and the model we reported in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, following a suggestion made by one of the reviewers, we have performed another robustness check, by using a testing procedure reported in Willis et al (2010) and predicted individual rationality at time 2 using just individual rationality at time 1 and group rationality as predictors (we controlled for age and gender as well). Although this statistical analysis does not address directly our two hypotheses, it allows us to compare the model fit for the simple model (procedure reported in Willis et al, 2010) and the model we reported in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Although this statistical analysis does not address directly our two hypotheses, it allows us to compare the model fit for the simple model (procedure reported in Willis et al, 2010) and the model we reported in Table 4. In order to obtain the scores for the Akaike's Information Criterion (AIC) and the Schwarz's Bayesian Criterion (BIS) we have run these additional analyses using the mixed models procedure in SPSS.…”
Section: Resultsmentioning
confidence: 99%
“…As noted above, preliminary risk assessments by experts and stakeholder engagement sessions narrowed the list of candidates [7]. Tables 1 and 2 list the pollutants for each exposure route-health endpoint combination.…”
Section: Methodsmentioning
confidence: 99%
“…Then, we presented the preliminary risk assessment results at workshops involving government environment and health officials, faculty at local universities, international experts, local industries, and environmental groups. Participants were led through a systematic process, developed through previous research, to prioritize the pollutant-exposure route combinations for consideration [7]. Stakeholder engagement in the selection of risks to consider was essential because the results were intended to inform future UAE strategic planning [8].…”
Section: Introductionmentioning
confidence: 99%
“…The first three components of this work are described elsewhere (Davidson et al 2011; Gibson 2011; Li et al 2010; MacDonald Gibson and Farah 2012; Willis et al 2010). …”
mentioning
confidence: 99%